2020
DOI: 10.1038/s41598-020-70675-x
|View full text |Cite
|
Sign up to set email alerts
|

Arginine as an environmental and metabolic cue for cyclic diguanylate signalling and biofilm formation in Pseudomonas putida

Abstract: Cyclic diguanylate (c-di-GMP) is a broadly conserved intracellular second messenger that influences different bacterial processes, including virulence, stress tolerance or social behaviours and biofilm development. Although in most cases the environmental cue that initiates the signal transduction cascade leading to changes in cellular c-di-GMP levels remains unknown, certain l - and d -amino acids have been described to modulate c-di-GMP turnover in some bacteria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 45 publications
(62 reference statements)
1
33
0
Order By: Relevance
“…The authors posited that the loss of SpuC caused physiological changes in the bacteria responsible for plant recognition, and that putrescine or its precursor, arginine, might be signalling molecules in the rhizosphere used by the bacteria to evade the plant immune response. This is consistent with recent results obtained by Barrientos‑Moreno et al indicating that arginine promotes biofilm formation through an increase in cyclic-di-GMP concentration [180] . Phase variation may also be used by rhizosphere Pseudomonas spp.…”
Section: Coping With Neighborssupporting
confidence: 94%
“…The authors posited that the loss of SpuC caused physiological changes in the bacteria responsible for plant recognition, and that putrescine or its precursor, arginine, might be signalling molecules in the rhizosphere used by the bacteria to evade the plant immune response. This is consistent with recent results obtained by Barrientos‑Moreno et al indicating that arginine promotes biofilm formation through an increase in cyclic-di-GMP concentration [180] . Phase variation may also be used by rhizosphere Pseudomonas spp.…”
Section: Coping With Neighborssupporting
confidence: 94%
“…Previous reports have established that hisP and genes involved in lysine catabolism are preferentially expressed in KT2440 in the rhizosphere of corn plants ( Espinosa-Urgel and Ramos, 2001 ; Matilla et al, 2007 ). In addition, a connection beween arginine transport and c-di-GMP signaling in this strain has been recently reported ( Barrientos-Moreno et al, 2020 ). These facts, and the influence of Rsm proteins on biofilm formation and surface motility, along with the identification of c-di-GMP turnover elements and other biofilm-related genes as targets of these proteins, made us analyze if mutants in rsm genes showed altered fitness in the rhizosphere.…”
Section: Resultsmentioning
confidence: 69%
“…In most cases, expression was enhanced in the mutant, indicating that the observed binding to their RNA targets leads to translation repression by these proteins; these results are consistent with previous observations on their influence upon biofilm-related elements (see below). However, the inverse was true for two of the tested fusions, those corresponding to PP_1088 ( argG , involved in arginine synthesis; Ramos-González et al, 2016 ) and PP_4482 (part of the gene cluster encoding the main arginine transporter and its regulator; Barrientos-Moreno et al, 2020 ). In these cases, expression was approximately halved in the mutant with respect to the wild type.…”
Section: Resultsmentioning
confidence: 98%
“…L-AAs are the dominant substrates for ribosome-based protein synthesis [ 25 ]. Barrientos-Moreno, Molina-Henares, Ramos-Gonzalez, and Espinosa-Urgel found that both exogenous and endogenous L-arginine affect biofilm formation of Pseudomonas putida through changes in cyclic diguanylate content, and altered expression of structural elements of the biofilm extracellular matrix [ 26 ]. Velmourougane and Prasanna revealed that since L-AAs (mainly L-Glu, L-Gln, L-His, L-Ser, L-Thr and L-Trp) affect the growth, aggregation, and carbohydrate synthesis of microorganisms, they are essential for the formation of biofilms [ 23 ].…”
Section: Discussionmentioning
confidence: 99%